The Performance of Cold-Formed Steel Beam-Column Connections with Screw Configuration - Mohamed, Saker; Setyowulan, Desy; Arifi, Eva (Rekayasa Sipil, 2024)
Cold-formed steel is being used as a viable substitute for traditional steel and building materials due to its performance, affordability, convenience, lightweight, and environmental friendliness. The major purpose of this current research is for a reaction to force-deformation at the connection level to be delivered, which is proper for typical cold-formed steel (CFS) screwed beam-column assembly CFS C-section, and to show the influence of the behavior of CFS under bending test. An inner plate, double angle plate, and self-drilling screws are used by a basic beam-column frame idealized CFS to join the beam-column. Fixed support was implemented at the column base, whereas the beam end had free support. A 0.75 mm cold-formed steel C-section with 80mm height and 30mm width was utilized in this study and assembled into an "I" and "box" configuration. 3d and 4d were used to compute screw spacing for self-drilling screws with 4 mm heads and 2 mm bodies. The first type was each angle plate (top and seat angle) screwed with eight screws, whereas the second involves four screws. The CFS section’s thinness led to the use of screw connections, which are essential to their ability to withstand connection failures, to anticipate the failure mode of the connection segment. Numerical simulation by ABAQUS Student Edition and analytical studies have been conducted by AS/NZS 4600:2018 to investigate the capacity of CFS under bending. Quantity and the arrangement of the screws determine the displacement ductility with tighter spacing enhancing performance and reinforcing global and local buckling resistance.